S Safety And Sustainable Public Transportation in The 21st Century - Ilham, Ilham (MSJ : Majority Science Journal, 2024)
This study examines the current prospects of sustainable and safe public transportation in Indonesia in the 21st century. Through a comprehensive literature review, this study analyzes the challenges and opportunities in implementing an effective public transportation system that prioritizes safety and sustainability. The main findings highlight the suboptimal condition of public transportation, the low willingness of the public to use public transportation as the primary mode of transportation, and the implementation of inconsistent policies. The study proposes strategies to improve public transportation's quality, safety and sustainability, including infrastructure improvements, public awareness campaigns, and policies to prevent the use of private vehicles. Stakeholder coordination, community involvement, and innovation development in the transportation sector are emphasized. This study concludes that realizing safe and sustainable public transportation in Indonesia requires a multifaceted and long-term approach involving governments at all levels, the private sector, and society. Continuous evaluation and adaptive policy-making are essential to develop context-appropriate solutions appropriate to Indonesia's diverse regions.